Managing Newspaper Collections in Public Universities In Ghana - Kwadzo, Gladys; Annor, Grace (Ghana Library Journal, 2013)
This study was to find out how state-owned or public universities in Ghana are managing their newspaper collections, from acquisition, processing, preservation to dissemination of newspaper information. The study was also to find out challenges encountered and offer recommendations. Data was collected from the eight public university libraries in Ghana using a questionnaire. Copies of the questionnaire were e-mailed to the libraries outside Accra whilst those in Accra were hand delivered. The study found that the numbers of newspapers acquired by the libraries vary but activities concerning their management were similar. The only method of preserving the collection was by binding. None of the libraries was digitizing their collection and it was only one library that adopted electronic means of indexing the newspaper information. All the activities undertaken by the libraries in managing their newspaper collections (except indexing done by one library electronically) were done manually. It is hoped that the findings will inform and encourage the libraries to pool together their efforts and resources to adopt modern methods of preservation (for example  digitizing) and managing the newspaper information for easy accessibility.